Regulatory network of ginsenoside biosynthesis under Ro stress in the hairy roots of Panax ginseng revealed by RNA sequencing - Meng, Xiangru; Zhang, Tao; Chen, Changbao; Li, Qiong; Liu, Jingwan (Frontiers in Bioengineering and Biotechnology, 2022)
Panax ginseng C.A. Meyer is a valuable Chinese herbal medicine that belongs to the Araliaceae family. Major obstacles to the continuous cropping of ginseng have severely restricted the sustainable development of the ginseng industry. The allelopathic effects of triterpenoid saponins play an important role in disorders related to continuous cropping; however, the mechanisms underlying the allelopathic autotoxicity of triterpenoid ginsenosides remain unknown. In this study, we performed mRNA and miRNA sequencing analyses to identify candidate genes and miRNAs that respond differentially to ginsenoside Ro stress in ginseng and their targets. The growth of the ginseng hairy roots was significantly inhibited under Ro stress (0.5 mg/L, Ro-0.5). The inhibition of root growth and injury to root-tip cells promoted the accumulation of the endogenous hormones indole-3-acetic acid and salicylic acid and inhibited the accumulation of abscisic acid and jasmonate acid. The accumulation of ginsenosides, except Rg3, was significantly inhibited under Ro-0.5 stress. An mRNA analysis of the Ro-0.5 and control groups showed that differentially expressed genes were mostly concentrated in the hormone signal transduction pathway. ARF7 and EFM were upregulated, whereas XTH23 and ZOX1 were downregulated. These genes represent important potential candidates for hormone-responsive continuous cropping diseases. In total, 74 differentially expressed miRNAs were identified based on the miRNA sequencing analysis, of which 22 were upregulated and 52 were downregulated. The target genes of ptc-miR156k_L+1, mtr-miR156b-5p, gma-miR156a_R+1, and mtr-miR156e all belonged to TRINITY_DN14567_c0_g4, which is a gene in the plant hormone signal transduction pathway. These four miRNAs were all negatively correlated with mRNA, indicating their likely involvement in the response of ginseng to continuous cropping disorders and the regulation of ginsenoside synthesis. Our findings provide useful insights for removing the barriers to continuous ginseng cropping and have important implications in the genetic engineering of plant stress responses.